Two simultaneous TriClip systems as a bailout technique - Manuel Luna-Morales; Fernando Carrasco-Chinchilla; Víctor Manuel Becerra-Muñoz; Juan Alonso-Briales; José María Hernández-García (REC: Interventional Cardiology (English Ed.))
A 66-year-old woman with severe functional tricuspid regurgitation and significant septal-anterior leaflet separation was admitted for transcatheter edge-to-edge repair. The patient’s prior informed consent was obtained for the intervention and subsequent publication of her case. A chorda tendinea ruptured during the implantation of the first TriClip XTW system (Abbott Laboratories, United States) leading to a prolapsed severe anterior leaflet and increased valvular regurgitation (figure 1, video 1 of the supplementary data). Therefore, we decided to implant multiple devices in a “zip-like” sequence. We implanted the first device close to the anteroseptal commissure, followed by a second XTW device, which was deployed more medially. However, the septal leaflet detached after removing the blockade and prior to its release (figure 2A). Given the risk of embolization, we stabilized the system, kept it static, and eventually accessed the contralateral femoral vein with yet another TriClip XT system (Abbott Laboratories, United States) (figure 2B-D, videos 2 and 3 of the supplementary data). We implanted a third TriClip XT system over the septal-posterior leaflets and released the 2 systems. We completed the procedure with the implantation of a final TriClip XT system between the second and third devices, with satisfactory results (figure 3, video 4 of...